منصة تسيير مواعيد لدى الهيئة الوطنية للرقابة التقنية للبناء - ايمن, زوزو; عبد العزيز, التجاني (Université of Eloued جامعة الوادي, 2026)
مؤخرا اصبحت ادارة المواعيد العمليات الفنية لدى هيئة الوطنية للرقابة التقنية للبناء CTC ذات اهمية كبيرة لضمان الكفاءة ولتنظيم ذلك تم اقتراح منصة الكترونية لتسيير المواعيد تهدف لستهيل عمل ادارة المواعيد ولانجاز هذا النظام اعتمدنا على : - تقنية UML لوصف مكونات واجزاء النظام - قواعد البيانات للحفاظ على معلومات آمنة و سليمة - استخدام لغات css و html و javascript و js.node لتصميم منصة الالكترونية Recently, the management of appointments and technical operations at the National Authority for Technical Control of Construction has become of great importance to ensure Efficiency.To organize this, a web platform for scheduling appointments was proposed, aiming to facilitate the work of appointment management. To complete this system, we relied on: - UML To describe the components and parts of the system design technique - Databases to keep information safe and sound - languages were used html, css, javascript and node.js to design the website
مذكرة تخرج سنة ثالثة ليسانس إعلام آلي
Keywords: بيانات قاعدة; UML; node.js; javascript; html; css; ويب تطبيق; Web application; data base